Ferrothermoconvective Instability of Soret-driven Convection in a Densely Packed Anisotropic Porous Medium - R. Sekar; D. Murugan; K. Raju (International Journal of Applied Methods in Electronics and Computers, 2016)
Ferrofluids find vast applications in various fields of science, agriculture, medicine and engineering. The Soret-driven ferrothermoconvective instability in an anisotropic porous medium heated from blow and salted from above has been analyzed using Darcy model for various parameters. To investigate the effect of vertical direction of anisotropy, the system is assumed to have vertical permeability different from that of the permeability along horizontal direction. A small thermal perturbation is imparted on the basic state and linear stability analysis is used for which normal mode technique is applied. It is found the presence of porous medium inhibits the convection and anisotropy favours the convection. The present work has been carried out through both oscillatory as well as stationary modes with graphical representation.